2012
DOI: 10.1159/000332147
|View full text |Cite
|
Sign up to set email alerts
|

Drug Allergy in Hospitalized Patients: The Contribution of Allergy Consultation and a Structured Questionnaire

Abstract: Background: Hospitalized patients with an alleged history of drug allergy pose medical and economic concerns when selecting medications for treatment, possibly leading to deviations from standards of care and the use of expensive agents. Accurate history taking and clear documentation of drug allergy are essential for preventing subsequent administration of the offending drug and overdiagnosis of drug allergy. We aimed to evaluate drug allergy-related history taking by internists compared to allergists and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In one study, 617 skin-prick test positive or negative patients with reported non-immediate reactions to penicillins were challenged orally with one-tenth of the normal dose of the antibiotic, followed by the full dose for 5 days. 1 Nine had an immediate mild rash without systemic symptoms and 608 (98.5%) had no reaction. Skinprick testing results did not predict reactions.…”
Section: β-Lactam Allergy De-labellingmentioning
confidence: 96%
“…In one study, 617 skin-prick test positive or negative patients with reported non-immediate reactions to penicillins were challenged orally with one-tenth of the normal dose of the antibiotic, followed by the full dose for 5 days. 1 Nine had an immediate mild rash without systemic symptoms and 608 (98.5%) had no reaction. Skinprick testing results did not predict reactions.…”
Section: β-Lactam Allergy De-labellingmentioning
confidence: 96%